Champ de spécialisation et revenu - Lacroix, Robert; Robillard, Paul; Lemelin, Clément (L'Actualité économique, 1978)
An earnings function is defined for the highly qualified manpower in Canada in 1973. Education, experience and field of study, instead of occupation, are the arguments. By use of regression techniques it is shown that the third independent variable adds significantly to the explanation of the variance of earnings. Even when years of schooling and experience are accounted for, the contribution of the so-called traditional fields of study—medicine, law, accounting and engineering—remains considerable. The first of the three interpretations suggested refers to different "innate" abilities associated with choice of a field of study but it is promptly dismissed. The second interpretation deals with differences in work organization leading to either more uncertain flows of earnings or to longer hours of work. It is shown to be plausible in the case of graduates of law schools but it does not hold in the case of graduates of medical schools. In the latter case a third interpretation is hinted at: medical doctors, either through their association or individually, do exert some significant influence on both the supply of and the demand for their own services.